The Application of Cooperative Learning Methods in Islamic Religious Education for Students with Special Needs in Inclusive Schools - Siti Julaeha; Muhammad Naelul Mubarok (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Inclusive education requires effective learning strategies to accommodate the diverse needs of students, including those with special needs. However, the implementation of Islamic Religious Education in inclusive classrooms often encounters challenges related to student participation, social interaction, and learning engagement. This study aims to analyze the implementation of cooperative learning methods in Islamic Religious Education for students with special needs at SMP PGRI 1 Ciputat, identify the supporting and inhibiting factors, and examine their impact on students. This research employed a qualitative field research approach with a descriptive design. Data were collected through observation, in-depth interviews, and documentation involving Islamic Religious Education teachers and Special Education Teachers as the primary informants. The data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings reveal that cooperative learning was implemented through heterogeneous group formation, group discussions, and the Student Teams Achievement Division (STAD) model. The implementation was supported by the school’s commitment to inclusive education, the presence of Special Education Teachers, positive attitudes of regular students, and teacher competence, while differences in students’ abilities, limited instructional time, and inadequate facilities became the main challenges. The study also found that cooperative learning improved students’ participation, self-confidence, social interaction, and learning motivation while strengthening Islamic values such as cooperation, responsibility, tolerance, and mutual respect. These findings demonstrate that cooperative learning is an effective strategy for supporting the academic, social, and spiritual development of students with special needs in inclusive Islamic Religious Education settings.